Kriyol syntax : the Portuguese-based Creole language of Guinea-Bissau - Kihm, Alain (Creole language library, 1994)
This book describes the Portuguese-based Creole which is widely spoken as a first language in Guinea-Bissau. The study focuses on one variety, 'central Kriyol', and its main aim is to present a complete description of the grammar of the language. The theoretical framework for the syntactic analysis is purposely eclectic but relies primarily on Generalized Phrase Structure Grammar, and ample attention is paid to the cognitive or semantic dimension in the explanation of linguistic facts. After a short introduction on the history and phonology of the language and the organization of the study, th.